2008
DOI: 10.1037/a0012795
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic priming in comprehension: The role of argument order and animacy.

Abstract: Two visual-world eye-movement experiments investigated the nature of syntactic priming during comprehension--specifically, whether the priming effects in ditransitive prepositional object (PO) and double object (DO) structures (e.g., "The wizard will send the poison to the prince/the prince the poison?") are due to anticipation of structural properties following the verb (send) in the target sentence or to anticipation of animacy properties of the first postverbal noun. Shortly following the target verb onset,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 41 publications
3
60
2
Order By: Relevance
“…In the behavioral and ERP literature, findings of syntactic priming in comprehension seem to be almost completely dependent on repetition of the head-word (Arai et al, 2007;Branigan et al, 2005;Carminati et al, 2008;Ledoux et al, 2007;Tooley et al, 2009;Traxler & Tooley, 2007). On the other hand, syntactic priming in production is often observed without lexical repetition (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the behavioral and ERP literature, findings of syntactic priming in comprehension seem to be almost completely dependent on repetition of the head-word (Arai et al, 2007;Branigan et al, 2005;Carminati et al, 2008;Ledoux et al, 2007;Tooley et al, 2009;Traxler & Tooley, 2007). On the other hand, syntactic priming in production is often observed without lexical repetition (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Bock, 1986;Bock & Loebell, 1990) or in faster speech onsets for repeated syntactic structures (Corley & Scheepers, 2002;Segaert, Menenti, Weber, & Hagoort, 2011;Smith & Wheeldon, 2001;Wheeldon & Smith, 2003;Wheeldon, Smith, & Apperly, 2011). Syntactic priming in comprehension is shown in anticipatory eye-movements to pictures (Arai, van Gompel, & Scheepers, 2007;Carminati, van Gompel, Scheepers, & Arai, 2008;Thothathiri & Snedeker, 2008a;Traxler, 2008), in faster reading (Traxler & Tooley, 2008) and in picture-matching choices for ambiguous phrases (Branigan, Pickering, & McLean, 2005). In comprehension tasks, ERP studies revealed the attenuation of the P600 amplitude as a result of syntactic priming (Ledoux, Traxler, & Swaab, 2007;Tooley, Traxler, & Swaab, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with their expectations, facilitation through the facial prime emerged rapidly (as soon as the sentence referenced one or the other IAPS picture) and occurred for the older adults with positive sentences only. For the younger adults, facilitation emerged with negative sentences only, and/or (depending on the time region considered) to a lesser extent for positive sentences (see [24] for a description of possible patterns consistent with a positivity effect and see [25,26] on gaze patterns reflecting processing facilitation).…”
Section: Positivity Biases In Emotional Priming Of Sentence Processingmentioning
confidence: 99%
“…In addition, the pervasiveness of animacy distinctions in human language (e.g., Comrie, 1989;Corbett, 1979;Dahl, 2008;Givón, 1976;Ransom, 1977;Zaenen et al, 2004), and the reliable influence of animacy on many sentence processing measures (e.g., Altmann & Kemper, 2006;Branigan et al, 2008;Carminati, van Gompel, Scheepers, & Arai, 2008;F. Ferreira, 1994; G. W. Humphreys et al, 2016;Szewczyk & Schriefers, 2011) would argue that, if HN-LN relatedness on any semantic feature is likely to have an influence on mismatch effects, it would be animacy.…”
Section: Experiments 3: Animacy Relatednessmentioning
confidence: 99%